Strategi Pengambilan Keputusan Kedai Kopi - Nawangsih Nawangsih; Kurniawan Yunus; Khoirul Ifa (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2019)
This study purpose to determine the influency of product quality, price, promotion and quality of service of partially and simultaneously on the consumer decision making process in choosing a coffee shop in Lumajang Regency. This research type is descriptive with a causal associative approach. This research using 100 respondents. The sampling technique used is Simple Random Sampling. Hypothesis testing using multiple linear regression analysis for hypotheses through the SPSS 21 for windows program. Results of the study showed that product quality, promotion and service quality there is a significant positive influency for partially on the decision making process of consumers in choosing a coffee shop in Lumajang Regency. The price of a positive influence is not significant to the consumer's decision making process in choosing a coffee shop in Lumajang Regency. Simultaneously product quality, price, promotion and service quality have a significant positive effect on the decision making process of consumers in choosing a coffee shop in Lumajang Regency. The variables studied affected 54.1% of the consumer decision making process in choosing a coffee shop in Lumajang Regency and the rest was influenced by another variables.